Yucatec Maya language planning and bilingual education in the Yucatan - Anne Marie Guerrettaz; Eric J. Johnson; Gisela Ernst-Slavit (Arizona State University, 2020)
The rapid decline of indigenous languages represents one of the most troubling topics within applied linguistics. Teachers' implementation of indigenous language planning through their pedagogical practices is a significant but under-researched issue. This ethnographic study examines a Maya language program (i.e., professional development) for 1,600 teachers in the Yucatan's Intercultural Bilingual Education (EIB) system, and K-12 schools in Maya-speaking communities where they worked. Using longitudinal data (2010-2016), analysis centered on the creation and promulgation of the Norms of Writing for the Maya Language (2014) and related language policy. Findings illustrate: 1) the importance of increasing the quantity of Maya-speaking teachers, and 2) a clash between widespread orthographic variation in Maya and teachers' standard language-culture. The new standard has not been implemented in EIB, which still does not in practice require Maya proficiency of teachers. This research discusses possible benefits and risks of a standard Maya for EIB.